Pain Correlates of Depressed Mood - Trudi M Walsh; Chloé P Smith; Patrick J McGrath (Pain Research and Management)
OBJECTIVE: To provide an initial indication of the intensity and quality of pain in young adults reporting depressed mood and to investigate possible underlying mechanisms.